Herbicidas postemergentes en yuca (Manihot esculenta Crantz) selectividad, metodos de aplicacion e interaccion con edad - Piedrahíta Castañeda, Wilson; Doll, J. (1974)
The herbicides dalapon, glyphosate, paraquat, MSMA, and diuron were evaluated for their postemergence selectivity in cassava (Manihot esculenta Crantz). Four methods of application were also tested: with a shield, directed without a shield, and hitting the lower 25 or 50 percent of the plant. In order to study the interaction between herbicide and plant age, the same products plus 2,4-D amine were applied to 40-65 and 90-day-old cassava, either over the top or to the lower half of the plant. Diuron was the only selective herbicide in over-the-top applications. Selectivity was greatly increased for all the herbicides tested by using a shield and directing the applications at the base of the plant. In all three ages, diuron was the most selective product. All the other products were highly toxic for all ages in over-the-top applications. Directing the spray at the lower half of the plant increased the selectivity of all the herbicides. (AS)